2013
DOI: 10.1063/1.4812987
|View full text |Cite|
|
Sign up to set email alerts
|

Kinase detection with gallium nitride based high electron mobility transistors

Abstract: A label-free kinase detection system was fabricated by the adsorption of gold nanoparticles functionalized with kinase inhibitor onto AlGaN/GaN high electron mobility transistors (HEMTs). The HEMTs were operated near threshold voltage due to the greatest sensitivity in this operational region. The Au NP/HEMT biosensor system electrically detected 1 pM SRC kinase in ionic solutions. These results are pertinent to drug development applications associated with kinase sensing. V C 2013 AIP Publishing LLC. [http://… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The main factor of the EG-AlGaN/GaN HEMT which may enhance the device performance in this situation, we suppose, is the sensing area. This is because it was reported that more surface receptors lead to a better electrical parameter of sensitivity, 24,25 and a larger sensing area has more receptors. In order to elucidate the relationship between the sensing area of the EG-AlGaN/GaN HEMT and its electrical characteristics, three different areas of the sensing pads were designed and modied (400 mm  400 mm, 500 mm  500 mm and 700 mm  700 mm).…”
Section: Discussion Of the Sensing Areamentioning
confidence: 99%
“…The main factor of the EG-AlGaN/GaN HEMT which may enhance the device performance in this situation, we suppose, is the sensing area. This is because it was reported that more surface receptors lead to a better electrical parameter of sensitivity, 24,25 and a larger sensing area has more receptors. In order to elucidate the relationship between the sensing area of the EG-AlGaN/GaN HEMT and its electrical characteristics, three different areas of the sensing pads were designed and modied (400 mm  400 mm, 500 mm  500 mm and 700 mm  700 mm).…”
Section: Discussion Of the Sensing Areamentioning
confidence: 99%
“…25 In a previous work, AuNPs were physically absorbed on the transistor surfaces for kinase detection. 26 The solution of AuNPs were spotted onto the wafer directly and dried in a vacuum desiccator. It was easy to cause aggregation and exfoliation from the surface.…”
Section: Introductionmentioning
confidence: 99%